Study of Contact Surface Roughness on Adhesive Performance in Steel and Aluminium Joints - Adviana, Febry; Ula, Shofiatul; Sunardi (DINAMIS, 2024)
Adhesive bonding is a technique widely used in various industries to join materials together. This process provides several advantages over traditional mechanical fastening methods, such as welding or nailing, including improved appearance, weight reduction, stress distribution, and the ability to join dissimilar materials. The advantages of adhesive bonding are simpler assembly, lightweight and lower production costs. This research is one of the developments of the glue adhesive connection method. The materials used in this research are 1100 series aluminium and low carbon steel where both are metals that we often encounter in everyday life. This study aims to analyse the effect of roughness treatment on the surface of each different test specimen using sandpaper with different roughness levels, namely 80 grit, 150 grit and 400 grit. The test conducted in this study was a tensile test to determine the maximum strength of the adhesive strength of each test specimen with ASTM D1002 test standards. The results showed that test specimen A with surface roughness treatment using 80 grit had a tensile strength of 0.2267, test specimen B with surface roughness treatment using 150 grit had a tensile strength of 0.168 and test specimen with 400 grit roughness treatment had a tensile strength of 0.0315.